Renal transplantation in children under 3 years of age: Experience from a single‐center study. (17th January 2018) - Loiseau, Yann; Bacchetta, Justine; Klich, Amna; Ranchin, Bruno; Demede, Delphine; Laurent, Audrey; Baudin, Florent; Garaix, Florentine; Roy, Pascal; Cochat, Pierre
Abstract: RTx remains challenging in children under 3 years of age. This single‐center study reviewed the medical records of children <3 years transplanted since 1987 (N = 32, Group 1). They were matched for donor type and RTx period with children aged 3‐13 years (N = 32, Group 2) and 13‐18 years (N = 32, Group 3). There were no between‐group significant differences regarding distributions of gender, primary renal disease, proportion of dialysis before RTx, and growth (SDS). Compared to Groups 2 and 3, Group 1 had more peritoneal dialyses ( P  < .001), more EBV mismatches ( P  = .04), and longer warm ischemia times ( P  < .001). The risk of graft loss was not significantly different among age groups (hazard ratio, 2.4 in Group 2 and 2.0 in Group 3 vs Group 1; P  = .2). Death occurred in four patients (3 in Group 1 and 1 in Group 2) and graft loss occurred in 28 patients, mainly due to chronic allograft nephropathy. In recipients <3 years of age, the outcomes of RTx are close to those obtained in older pediatric age groups. Thus, young patients may be transplanted in experienced multidisciplinary teams without additional risks provided that particular attention is paid to donor selection and prevention/early diagnosis of comorbidities and complications.